478 Dietary Butyrate and Valerate Glycerides: Effects on Growth and Systemic Immunity of Weanling Piglets Coinfected with F4 and F18 Escherichia coli. (8th October 2021) - Kovanda, Lauren L; Park, Jungjae; He, Yijie; Park, Sangwoo; Wu, Ruochen; Wong, Braden; Kim, Kwangwook; Liu, Yanhong
Abstract: Enterotoxigenic Escherichia coli (ETEC) F4 and F18 are the two most dominant pathogenic strains in weaned pigs. The objective of this experiment was to test the effects of dietary monobutyrin and monovalerin on performance and systemic immunity of weanling piglets coinfected with F4/F18 ETEC. Twenty weaned pigs (8.21 ± 1.23 kg) were individually housed and were randomly allotted to one of three diets: control (n = 6), 0.1% monobutyrin (n = 7), or 0.1% monovalerin (n = 7). The experiment was conducted 14 days, including 7 days' adaption and 7 days post-inoculation (PI). On d 0, d 1, and d 2 PI, pigs were inoculated with 0.5 × 10 9 CFU/1.5 mL each of F4 and F18 ETEC for three consecutive days. Diarrhea score was recorded daily to determine frequency of diarrhea. Piglets and feeders were weighed throughout the trial to analyze growth performance. Fecal cultures from pigs on d 0, 2, and 4 PI were inspected to identify the absence or presence of hemolytic coliforms. Blood was collected on d 0, 4, and 7 PI for complete blood cells count. All data were analyzed by the Proc Mixed of SAS with randomized complete block design. Pigs supplemented with monovalerin and monobutyrin had numerically higher ADG (249 and 282 g/day) from d 0 to d 7 PI than pigs in control (198 g/day). Supplementation of monovalerin reduced (P < 0.05) frequency of diarrhea throughout the experiment. Pigs fed monovalerin had lower (P < 0.05) neutrophil counts on d 4 PI compared with control. Hemolytic coliforms were observed in all fecal cultures from d 2 and d 4 PI, confirming fecal shedding of ETEC. Results of this study indicate the potential benefits of monovalerin supplementation on performance and disease resistance of weaned pigs coinfected with F4 and F8 ETEC.